Analisis Determinan Perilaku Keselamatan Berkendara (Safety Riding) pada Ojek Online (Maxim) di Pangkalan Ojek Motor Jl. Untung Suropati Kota Samarinda - Dwi Andre Gustian Prayugo; Nino Adib Chifdillah; Emelia Tonapa (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Traffic and road accidents are considered one of the leading causes of death among children and adolescents aged 5-29 years. This study aims to analyze the relationship between age, education level, driving experience, and knowledge with safety riding behavior among motorcycle taxi riders at the MAXIM Online Ojek Base on Jl. Untung Suropati, Samarinda City. The research method used in this study is a quantitative research approach. This type of research is observational-analytic with a cross-sectional design. The sampling technique used is purposive sampling, where samples are selected based on criteria predetermined by the researcher. The total sample consists of 37 individuals, determined using the total sampling technique. Data analysis was conducted using the Chi-Square test. The results show that there is a relationship between age and knowledge with respondents' safety riding behavior. However, there is no relationship between driving experience and education level with respondents' safety riding behavior. In conclusion, it is recommended that motorcycle taxi riders improve their knowledge of proper safety riding practices.